La estela de la pluma Cultura impresa e intelectuales en Centroamérica durante los siglos XIX y XX - Molina Jiménez, Iván (Editorial Universidad Nacional (EUNA), 2004)
The studies included in this book examine popular literacy, the expansion of the trade in book and pamphlet production, and the dynamics of intellectual circles in 19th and 20th century Central America. The work, by concentrating on some of the main cultural changes that the isthmus experienced during the indicated period, explores hitherto little-known dimensions of its past, which are essential to understanding its complex and conflictual history.